Acylphloroglucinol derivatives from the twigs and leaves of Callistemon salignus. Issue 14 (6th April 2017) - Qin, Xu-Jie; Liu, Hui; Yu, Qian; Yan, Huan; Tang, Jin-Feng; An, Lin-Kun; Khan, Afsar; Chen, Qi-Run; Hao, Xiao-Jiang; Liu, Hai-Yang
Abstract: Three new acylphloroglucinol derivatives, callisalignones A–C (1 –3 ), six new meroterpenoids, callisalignenes A–F (4 –9 ), along with 18 known analogues (10 –27 ) were isolated from the twigs and leaves of Callistemon salignus . Their structures and absolute configurations were established by comprehensive spectroscopic evidences (NMR, MS, amd electronic circular dichroism calculations). The absolute configurations of callistenones B (13 ) and H (14 ) were determined by comparison of their ECD spectra with that of callisalignone B (2 ). Callisalignones B and C are new adducts of β -triketone and acylphloroglucinol, whereas callisalignenes A–D are new meroterpenoids of acylphloroglucinol and α -phellandrene with different coupling models via hetero-Diels-Alder reaction, respectively. Myrtucommulone D (15 ) showed significant antibacterial activity against Staphylococcus aureus and three drug resistant S. aureus strains with MIC values of 1.953 and 0.975 μg/mL, respectively. Isomyrtucommulone B (17 ) displayed remarkable antibacterial activity against Escherichia coli with an MIC value of 0.122 μg/mL. Cytotoxic assay revealed that isomyrtucommulone B (17 ) was the most active against HCT116 with an IC50 value of 2.09 ± 0.10 μM. Graphical abstract: